National Identity Narratives In History: History Textbooks And Media Discourse In Central Asia - Khamzina, Guldana (Nazarbayev University, Graduate School of Public Policy, 2023)
After gaining independence in 1991, the question of national identity has become one of the challenges in Central Asia. As newly emerged countries, each state took different directions in conceptualizing the notion of national identity. In this dissertation, I conduct a comparative analysis of discourses and narratives on national identity shaped through national history writings in Kazakhstan, Kyrgyzstan, and Uzbekistan. I focus on defining the state's role in building and promoting the idea of national unity under a single shared national identity. As the nature of constructing national identity is fluid and perplexing by nature, I attempt to explore the nature of national identity construct built through national history writing of these states. The research applies qualitative research methods: discourse and narrative analysis, semiotics, and semi-structured interview. For this research, I collected data from three domains. The first is history textbooks in public education. The second domain was the state-supported newspaper articles published from 1991 to December 2021. The third data set came from the interviews conducted with historians and experts in national history writing. The collected data were in four languages in Kazakh, Kyrgyz, Uzbek, and Russian. This thesis contributes to understanding how the selected states employed history in creating and building the concepts of national identity. As the research incorporates data in the main languages spoken in the countries, this thesis comprehensively analyzes the discourses of national identity built in the last 30 years. The findings of discourse analysis show the evaluation of national identity concepts in the region throughout these years: from contested and publicly discussed notions to the more state-controlled narratives of national identity. Moreover, the development of grand narratives of national identity in history was heavily supported by the states. The examination of the textbooks and interview findings present the state's efforts in building national history writing culture.
Keywords: Type of access: Embargo